Application Value of NT-proBNP Combined with NLR in Evaluation of Major Adverse Cardiac Events in Elderly Patients with Chronic Heart Failure. (14th October 2022) - Li, Zhiyong; Rong, Hui; Wu, Wenxun; Huang, Ting; Xu, Jun
Abstract : Objective . To explore the application value of N-terminal pro-B type natriuretic peptide (NT-proBNP) combined with neutrophil-to-lymphocyte ratio (NLR) in evaluation of major adverse cardiac events (MACEs) in elderly patients with chronic heart failure (CHF). Methods . 50 CHF patients admitted to the Department of Cardiovascular Medicine of our hospital from January 2021 to December 2021 were selected as the observation group. Another 50 non-CHF patients of our hospital were selected as the control group. Clinical data were collected from subjects who met the inclusion criteria, including general information, personal disease history, and laboratory test indicators. Patients with CHF were followed up for 6 months. Patients with CHF were divided into two groups, MACE group and non-MACE group. Results . The levels of WBC, NEU, NLR, and NT-proBNP in observation group were higher than those in control group, but the level of LYM was the opposite (P < 0.05 ). The age, WBC, NEU, LYM, PLT, blood glucose, NLR, and NT-proBNP of MACE group and non-MACE group were significantly different (P < 0.05 ). The increased levels of NEU, NLR, NT-proBNP and the decreased levels of LYM and PLT are all independent risk factors for MACE in elderly patients with CHF (P < 0.05 ). The AUC of NLR in evaluating the occurrence of MACE in elderly CHF patients was 0.841. When the Youden index was 0.7692, the sensitivity was 76.92% and the specificity was 100.00%. The AUC of NT-proBNP in evaluating the occurrence of MACE in elderly CHF patients was 0.705. When the Youden index was 0.5260, the sensitivity was 76.92% and the specificity was 75.68%. The AUC of NT-proBNP combined with NLR in evaluating the occurrence of MACE in elderly CHF patients was 0.954. When the Youden index was 0.8420, the sensitivity was 92.31% and the specificity was 91.89%. Conclusion . NT-proBNP combined with NLR has high value in the evaluation of MACE in elderly CHF patients and can be used as an auxiliary predictive index in clinic.